2016
DOI: 10.1109/thms.2015.2480801
|View full text |Cite
|
Sign up to set email alerts
|

Human Interaction With Robot Swarms: A Survey

Abstract: Abstract-Recent advances in technology are delivering robots of reduced size and cost. A natural outgrowth of these advances are systems comprised of large numbers of robots that collaborate autonomously in diverse applications. Research on effective autonomous control of such systems, commonly called swarms, has increased dramatically in recent years and received attention from many domains, such as bioinspired robotics and control theory. These kinds of distributed systems present novel challenges for the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
216
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(226 citation statements)
references
References 126 publications
1
216
0
2
Order By: Relevance
“…A recent survey on human interaction with robotic swarms is available in [8]. One of the most frequently studied questions in human-swarm interaction is the design of appropriate control inputs for swarms.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent survey on human interaction with robotic swarms is available in [8]. One of the most frequently studied questions in human-swarm interaction is the design of appropriate control inputs for swarms.…”
Section: Related Workmentioning
confidence: 99%
“…One of the most frequently studied questions in human-swarm interaction is the design of appropriate control inputs for swarms. Four basic control approaches are distinguished in [8]: (1) algorithm switching; (2) parameter changing; (3) indirect control through environment influence; and (4) control through selected leaders. In our study we utilize algorithm switching and control through teleoperated leaders.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These examples do not constitute an exhaustive review of the literature. For a more comprehensive survey, we refer the reader to Kolling et al (2016).…”
Section: Related Literaturementioning
confidence: 99%
“…The user may also take direct control of individual units of the swarm, thereby influencing its dynamics indirectly. A recent survey on HSI research can be found in Kolling et al (2016).…”
Section: Ocbotics Interfacesmentioning
confidence: 99%